Visuals worth spreading: o design que comunica os eventos TEDx - Dausacker, Lucas Dalvan (Universidade do Vale do Rio dos Sinos, 2018)
This graduation final project seeks to investigate the design practices employed by the global brand TED, by structuring a network of independently events under its extension called TEDx. The main axis of the methodological strategy, inspired by cartography, analyzes the proposed theme from two perspectives. In the first phase, we will present a look at the visual language and the design practices that transcribe it. Next in the second phase, we will try to understand the social meaning built by the branding structures adopted by the brand. By crossing these two perspectives, a narrative that analyzes the visuality of the TEDx events will be suggested, pointing out design features that role as strategy of adaptation and amplification of the his messages to the medium. Finally, a sequence of reflections will be presented tracing a network that seems to be structured both by its visuality and its meaning.
Keywords: TED; TEDx; Design; Branding; Identidade visual; Comunicação; Redes; Visual Identity; Communication; Networks